THE PECULIARITIES OF THE INFORMATION EXCHANGE PROCESS - Rakhimova Shakhnoza Anvarovna; Khamrayeva Gulnoz Rustamovna; Sultanova Zukhra Shukhratovna; Xakimova Laziza Yusupovna (Utilitas Mathematica, 2025)
This article describes information, the essence of information, characteristics of information exchange processes, regulatory functions, micro, meso and macro levels. In addition, an analysis of the positive and negative aspects of information exchange through social networks and messengers is provided. Scientific conclusions are given on the results of the research of the information exchange process.